"You Never Know What's Gonna Happen": An Examination of Communication Strategies Used by College Student-Athletes to Manage Uncertainty. (December 2015) - Romo, Lynsey Kluever; Davis, Christine; Fea, Alyssa
Student-athletes are regularly faced with uncertainty, particularly at the highest levels of collegiate sports. Although it can result in both adverse and beneficial outcomes, little is known about the nature of this uncertainty. Thus, framed by Uncertainty Management Theory (UMT), this study relied on in-depth interviews of 17 student-athletes at an athletically-and-academically elite U.S. university to uncover what uncertainty scholar-athletes encountered and how they managed this ambiguity communicatively. The investigation found student-athletes experienced personal (e.g., injury), social (e.g., friends), and future (e.g., career) uncertainty. Participants managed this uncertainty through the use of communication strategies such as seeking social support, not disclosing their athlete status, or relying on prayer. While most participants perceived uncertainty as negative and sought to reduce it, some embraced it and learned to adapt. In addition to uncovering tangible uncertainty management strategies, the study recommends that college athletics departments implement several measures to address uncertainty.